Proceso de atención de enfermería en paciente adulto con pie diabético necrotizado. - Solís Moncada, Zaida Katherine (2022)
Necrotized diabetic foot is one of the pathologies with the highest risk worldwide, since inadequate control can produce neurological alterations and infections in the tissue. This disease is the result of the lack of insulin production from the pancreas, therefore, blood glucose levels rise. Ulcers caused on the foot are one of the most frequent complications with a diagnosis of Diabetes Mellitus, with 15% of the population and tend to have between 15 to 40 times more risk of amputations due to the amount of necrotized tissue. One of the activities that nursing carries out within this pathology is patient education on the care they should have with ulcers, to prevent them from having complications that threaten their well-being. The total annual incidence is 2-3% and 7% in patients with neuropathy. After amputation in the lower extremity, the incidence of a new ulcer and/or contralateral amputation at 2-5 years is 50% and survival after radical surgery will be 50% and 40% at 3 and 5 years. The present clinical case is carried out in order to analyze the consequences of Diabetes Mellitus, as well as to make the patient a participant in the care and control of their pathology, with the nursing staff having a fundamental role in said care, based on the promotion and disease prevention.